2017
DOI: 10.1038/srep42304
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral sensory neuron injury contributes to neuropathic pain in experimental autoimmune encephalomyelitis

Abstract: Multiple sclerosis (MS)-induced neuropathic pain deteriorates quality of life in patients but is often refractory to treatment. In experimental autoimmune encephalomyelitis (EAE), a rodent model of MS, animals develop neuropathy and inflammation-induced tissue acidosis, which suggests the involvement of acid-sensing ion channels (ASICs). Also, peripheral neuropathy is reported in MS patients. However, the involvement of the peripheral nervous system (PNS) in MS neuropathic pain remains elusive. This study inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 67 publications
3
20
0
Order By: Relevance
“…despite no change in clinical EAE. Similar to other EAE studies (Duffy et al, 2016;Frezel et al, 2016;Wang et al, 2017), our findings further support the idea that pain behaviors are independent of clinical severity in EAE. Additionally, our results are consistent with a previous report demonstrating that intrathecal injection of CD4 ϩ CD25 ϩ Treg cells relieves mechanical allodynia in mice treated with the chemotherapeutic paclitaxel (Liu et al, 2014).…”
Section: Discussionsupporting
confidence: 90%
“…despite no change in clinical EAE. Similar to other EAE studies (Duffy et al, 2016;Frezel et al, 2016;Wang et al, 2017), our findings further support the idea that pain behaviors are independent of clinical severity in EAE. Additionally, our results are consistent with a previous report demonstrating that intrathecal injection of CD4 ϩ CD25 ϩ Treg cells relieves mechanical allodynia in mice treated with the chemotherapeutic paclitaxel (Liu et al, 2014).…”
Section: Discussionsupporting
confidence: 90%
“…We hypothesized that in the context of peripheral neuropathy, advillin would be detectable in cerebrospinal fluid (CSF) if advillin-associated nascent focal adhesions are shed during active neurite retraction accompanied by axonal regeneration. We analyzed the CSF of naïve mice and EAE mice, a mouse model of multiple sclerosis that shows severe peripheral neuropathy associated with IB4 + sensory neurons ( 23 ). Advillin and myosin IIa protein was detectable in the CSF of EAE mice in the recovery phase, defined as after day 30 in the EAE model, with score 3 or higher, but was not detectable in naïve healthy mice ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…IB4 + DRG neurons belong to the nonpeptidergic nociceptors that are largely involved in pain associated with peripheral neuropathy induced by chemotherapy, chronic constriction, and EAE ( 23 , 35 , 36 ). For example, nerve injury-induced mechanical allodynia is significantly reduced when IB4-binding afferent neurons are specifically deleted by the toxin saporin ( 37 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Peripheral IL-6 increases TRPV-1 expression in dorsal root ganglion neurons and causes sensitization of unmyelinated sensory fibers, leading to various types of pathological pain (Brenn et al, 2007;Fang et al, 2015). It has been recently reported that myelin disruption and injured neurons are observed in the peripheral nervous system of EAE mice, suggesting that peripheral neuropathy is involved in EAEinduced neuropathic pain (Wang et al, 2017). In contrast, Olechowski et al indicated that sensory neuropeptides such as calcitonin gene-related peptide and galanin were not changed in EAE mice (Olechowski et al, 2009).…”
Section: Tablementioning
confidence: 99%